Metal-free approach towards efficient synthesis of FDCA using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst and oxone over two steps from HMF, fructose and glucose - Tamboli, Asma T. Biradar; Kirdant, Swapnali P.; Jadhav, Vrushali H. (New Journal of Chemistry, 2022)
In this work, a metal-free approach towards the synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF), fructose and glucose is reported over two steps using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst (p-TSA-POM) in the first step and oxone as an oxidant in the second step. HMF, fructose and glucose were converted to 2,5-diformylfuran (DFF) using the p-TSA-POM catalyst followed by oxidation of DFF to FDCA using oxone. To the best of our knowledge, this is the first metal-free approach for the synthesis of FDCA directly from glucose. DFF was obtained from HMF in 91% yield, whereas it was obtained in 85% and 61% yields from fructose & glucose, respectively. DFF was further converted to FDCA using oxone as an oxidant. FDCA was obtained in an overall yield of 84%, 78% and 56% from HMF, fructose & glucose, respectively.

Modification of some steps in the synthesis of Ivacaftor by mechano-chemical approach - Bankar, Shubham R.; Jadhav, Vrushali H. (Sustainable Chemistry for Climate Action, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Recently implementation of the mechano-chemistry approach for carrying out some of the steps in the synthesis of API’s, is considered an attractive and environment friendly approach as it permits solvent-free reactions or the use of activators for the reaction, making the process efficient and economical. In this study, we focused on the modification of some steps in the drug Ivacaftor, which is one of the most expensive drugs in the market. For the first time, a mechano-chemical approach was employed to replace some steps in the synthesis of Ivacaftor. One of the fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) required in the synthesis of Ivacaftor was prepared in two steps from commercially available 2, 4-bis(1,1-dimethylethyl)-5-nitrophenyl methyl carbonate (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">6<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) by mechano-chemistry approach in good yields. In the last step, fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) was coupled with 4-quinolone-3-carboxylic acid <span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">(4)<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> using mechano-chemistry to obtain Ivacaftor (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">1<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) in good yields. The advantage of this methodology was it avoided the use of solvent in all three steps of ivacaftor synthesis, making the process efficient and economical.